La linguistique cognitive et Humboldt - Anne-Marie Chabrolle-Cerretini (Corela, 2007)
This article goes into the Humboldt’s affiliations or posterity, even though we should consider that we have here complex affiliations and a posterity more « confused » than it seems. In this spirit, the article shows Humboldt’s influence on North American linguistics, and in particular on the two great representatives of anthropological linguistics: Sapir and Whorf. The article next aims at (1) enlarging the exposé and (2) returning to what best characterizes the Humboldtian model, in order to analyse how we should understand the link uniting language and culture(s). Here again, however, it is more complex than it appears, knowing on the one hand that this link between language and culture(s) is not « representationalist », and that cultures must indeed be envisaged in the plural, in all their diversity.